THE POTENCY OF DAIRY CATTLE AGRIBUSINESS DEVELOPMENT IN SEMARANG REGENCY, CENTRAL JAVA - Mukson, M.; Ekowati, T.; Handayani, M.; Gayatri, S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The study aimed to analyze the potency of dairy cattle agribusiness development in SemarangRegency and the factors influencing the potency of dairy cattle agribusiness development. The studywas conducted from September to December 2008 in Semarang Regency, Central Java, using surveymethod. Three districts were purposively chosen based on the largest population of dairy cattle in theSemarang Regency. Of the three districts selected, six villages were chosen based on the largestpopulation of dairy cattle. The respondents were chosen randomly using simple random, hence thesample size in this study was 90. Data were gathered through primary and secondary data. The data wereanalyzed descriptively and statistically. The analysis of LQ (Location Quotient) was used to analyze thepotency of dairy cattle agribusiness development, while the multiple regression model was used todetermine the factors affecting the potency of dairy cattle agribusiness development, with the followingregression equation: Y = a + b1x1 + b2x2 + b3x3 + b4x4 + b5x5 b7x7 b6x6 + + + e, whereas Y = is theproduction of milk, and x1 to X7, respectively, are x1 (age), x2 (education), x3 (Number of familymembers), x4 (number of lactating cows), x5 ( amount of feed, forage), x6 (amount of feed concentrate)and X7 (calving interval). The results showed that the potency of dairy cattle agribusiness developmentin Semarang Regency is potential (LQ> 1) with the value of 4.67 and LQ Population GDP = 1.71. Thisstudy indicated that socio, economic and demographic resources are important factors that can helpdevelop and improve dairy cattle farming. Meanwhile, there were significant relationships between 7independent factors and the potency of dairy cattle agribusiness development, with the followingregression equation: Y = -6.082 + 0.032 x1 + 0.223 x2 + 0.717 x3 + 9.221 x4 + 0.067 x5 x6 + 0.486 -0.323 X7 + e. Moreover, the value of R2 = 0.886, it is indicated that 88.6% of the variation in the thedependent variable can be explained by the independent variable, only 11.40% can be explained by othervariables.